Inovasi Supervisi Pendidikan Berbasis Teknologi di Era Digital untuk Mempersiapkan Sistem Pendidikan Masa Depan - Aninda Tri Safinatun Najah; Moch. Chafiid Dhuha (MASALIQ, 2026)
Although technology-based educational supervision has received attention in various studies, studies that specifically integrate supervisory innovation within the framework of preparing future education systems remain limited. This study aims to analyze technology-based innovations in educational supervision in the digital era in supporting the improvement of supervision quality and the readiness of future education systems. This study employed a qualitative approach with a library research design, using various relevant scholarly literature sources, such as books, journal articles, and policy documents. Data were collected through documentation study and analyzed using content analysis techniques. The results show that technology-based supervision is able to improve the effectiveness, efficiency, and objectivity of the supervision process, particularly in evaluating teacher performance, improving learning quality, and making educational decisions. These findings contribute to the development of the concept of modern digital-based educational supervision while broadening understanding of the transformation of education systems in the technological era. This study affirms that the integration of technology in educational supervision is an important element in building a future education system that is adaptive, collaborative, and data-driven, and also has practical implications for principals, supervisors, and policymakers in optimizing the implementation of technology-based supervision in educational institutions.